2004
DOI: 10.1007/bf03350903
|View full text |Cite
|
Sign up to set email alerts
|

Utility of combined use of plasma levels of chromogranin A and pancreatic polypeptide in the diagnosis of gastrointestinal and pancreatic endocrine tumors

Abstract: The combined assessment of PP and CgA leads to a significant increase in sensitivity in the diagnosis of GEP tumors, particularly in pancreatic NF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 22 publications
2
62
1
Order By: Relevance
“…The most critical discrepancies were (a) the composition of the case groups, with the strongest difference being represented by the fact that some studies included NEN from all sites (Bernini et al 2001, Donica et al 2010, Molina et al 2011, Korse et al 2012, Marotta et al 2012, Tohmola et al 2014, whereas some others tried to analyze more homogeneous set of patients, mainly selecting gastroenteropancreatic tumors (Tomassetti et al 2001a, Peracchi et al 2003, Nehar et al 2004, Zatelli et al 2007, Belli et al 2009, Modlin et al 2013 (Table 1); (b) the composition of the control groups: although the majority of studies used healthy subjects as controls (Bernini et al 2001, Tomassetti et al 2001b, Peracchi et al 2003, Nehar et al 2004, Campana et al 2007, Zatelli et al 2007, Belli et al 2009, Donica et al 2010, Molina et al 2011, Korse et al 2012, which represents the best approach to assess the diagnostic performance of a marker (Shapiro 1999), some researchers determined the metrics of circulating CgA by comparing NEN with non-NEN tumors (Nobels et al 1998, Panzuto et al 2004 or active versus diseasefree NEN (Bajetta et al 1999, Panzuto et al 2004; (c) the consideration of interfering factors: some authors tried to clean up the control group from those conditions with known effect on CgA levels, thus obtaining a more pristine evaluation of marker specificity (Bernini et al 2001, Tomassetti et al 2001b, Nehar et al 2004, Campana et al 2007…”
Section: Circulating Cga In the Diagnostic Phase Of Nenmentioning
confidence: 99%
See 1 more Smart Citation
“…The most critical discrepancies were (a) the composition of the case groups, with the strongest difference being represented by the fact that some studies included NEN from all sites (Bernini et al 2001, Donica et al 2010, Molina et al 2011, Korse et al 2012, Marotta et al 2012, Tohmola et al 2014, whereas some others tried to analyze more homogeneous set of patients, mainly selecting gastroenteropancreatic tumors (Tomassetti et al 2001a, Peracchi et al 2003, Nehar et al 2004, Zatelli et al 2007, Belli et al 2009, Modlin et al 2013 (Table 1); (b) the composition of the control groups: although the majority of studies used healthy subjects as controls (Bernini et al 2001, Tomassetti et al 2001b, Peracchi et al 2003, Nehar et al 2004, Campana et al 2007, Zatelli et al 2007, Belli et al 2009, Donica et al 2010, Molina et al 2011, Korse et al 2012, which represents the best approach to assess the diagnostic performance of a marker (Shapiro 1999), some researchers determined the metrics of circulating CgA by comparing NEN with non-NEN tumors (Nobels et al 1998, Panzuto et al 2004 or active versus diseasefree NEN (Bajetta et al 1999, Panzuto et al 2004; (c) the consideration of interfering factors: some authors tried to clean up the control group from those conditions with known effect on CgA levels, thus obtaining a more pristine evaluation of marker specificity (Bernini et al 2001, Tomassetti et al 2001b, Nehar et al 2004, Campana et al 2007…”
Section: Circulating Cga In the Diagnostic Phase Of Nenmentioning
confidence: 99%
“…By contrast, there are some tumors showing CgA elevation where the presence of histological neuroendocrine differentiation has not been reported, such as primary hepatocellular cancer (Spadaro et al 2005) and breast cancer (Giovanella et al 2001). To date, the capability of circulating CgA in discriminating NEN from other malignancies has been evaluated by many studies, which reported controversial results characterized by wide variation of specificity values (Nobels et al 1998, Nehar et al 2004, Panzuto et al 2004, Molina et al 2011, Marotta et al 2012 (Table 3). This was likely due to the heterogeneity of both NEN groups and neoplastic controls, with the latter including different tumor types.…”
Section: Oncological Causes Of Cga Elevationmentioning
confidence: 99%
“…Furthermore, pheochromocytoma or paraganglioma in the pancreas, to a certain extent, is a type of pancreatic neuroendocrine tumor (pNET), which means that the tumor cells of resected tumors may demonstrate positive reactions for CgA and Syn following immunohistochemical staining (12). With regard to the first two cases presented here, this pathological feature is of significant value for histological diagnosis of pancreatic pheochromocytoma.…”
Section: Discussionmentioning
confidence: 72%
“…• Chromogranin A (CgA) 67-93% [8] 85-88% [8] • Chromogranin B (CgB) 57% [19] 100% [19] Neuronspecifi kus enoláz (NSE) 100% [9] 32,9% [9] Pancreaspolipeptid (PP) 54-57% [33] 81% [33] …”
Section: Chromograninokmentioning
confidence: 99%